Memória da atuação política do movimento estudantil em Goiânia no período da Ditadura Civil-Militar (1964-1968) - Fideles, Eduarda Sousa (2024)
The present research aims to investigate the struggles and demonstrations of high school students who studied at Lyceu de Goiânia and Professor Pedro Gomes schools, as well as university students from the Federal University of Goiás (UFG) during the period of the Civil-Military Dictatorship (1964-1968) in Goiás, especially in the capital, Goiânia. The sources used consist of written documents and newspapers from that time, in order to analyze the actions and demonstrations organized and carried out by students as a form of political struggle and intervention. The study focuses on the dictatorial regime and educational policies, highlighting the political, educational, cultural, and social aspects related to the respective schools. Additionally, it seeks to reflect on the construction of the memory of these individuals through the testimonies of some high school students and young university students, known as former militants, who participated in and led the resistance movements of the time